Exogenous ketone supplementation and keto-adaptation for endurance performance: disentangling the effects of two distinct metabolic states - Shaw, D. M.; Merien, F.; Braakhuis, A.; Maunder, E.; Dulson, D. K. (Sports Medicine, 2020)
Ketone bodies (KB) provide an alternative energy source and uniquely modulate substrate metabolism during endurance exercise. Nutritional ketosis (blood KBs >?0.5 mM) can be achieved within minutes via exogenous ketone supplementation or days-to-weeks via conforming to a very low-carbohydrate, ketogenic diet (KD). In contrast to short-term (< 2 weeks) KD ingestion, chronic adherence (> 3 weeks) leads to a state of keto-adaptation. However, despite elevating blood KBs to similar concentrations, exogenous ketone supplementation and keto-adaptation are not similar metabolic states as they elicit diverse and distinct effects on substrate availability and metabolism during exercise; meaning that their influence on endurance exercise performance is different. In contrast to contemporary, high(er)-carbohydrate fuelling strategies, inducing nutritional ketosis is rarely ergogenic irrespective of origin and, in fact, can impair endurance performance. Nonetheless, exogenous ketone supplementation and keto-adaptation possess utility for select endurance events and individuals, thus warranting further research into their performance effects and potential strategies for their optimisation. It is critical, however, that future research considers the limitations of measuring blood KB concentrations and their utilisation, and assess the effect of nutritional ketosis on performance using exercise protocols reflective of real-world competition. Furthermore, to reliably assess the effects of keto-adaptation, rigorous dietary-training controls of sufficient duration should be prioritised.